Discovery of a Novel and Potent Dual-Targeting Inhibitor of ATM and HDAC2 Through Structure-Based Virtual Screening for the Treatment of Testicular Cancer - Ruan Y; Guan L; Wang Y; Geng Y; Wang X; Niu MM; Yang L; Xu C; Xu Z (Dove Medical Press, 2024)
Yashi Ruan,1,* Lixia Guan,2,* Yuting Wang,2 Yifei Geng,2 Xiaoran Wang,2 Miao-Miao Niu,2 Li Yang,1 Cen Xu,1 Zhen Xu1 1Department of Urology, Reproductive Medicine and Oncology, The Affiliated Taizhou People's Hospital of Nanjing Medical University, Taizhou, 225300, People's Republic of China; 2Department of Pharmaceutical Analysis, China Pharmaceutical University, Nanjing, 211198, People's Republic of China*These authors contributed equally to this workCorrespondence: Li Yang; Cen Xu, Department of Urology, Reproductive Medicine and Oncology, The Affiliated Taizhou People's Hospital of Nanjing Medical University, Taizhou, 225300, People's Republic of China, Email proyangli@163.com; cenxu263128@163.comPurpose: Dual inhibition of ataxia telangiectasia mutated (ATM) and histone deacetylase 2 (HDAC2) may be a potential strategy to improve antitumor efficacy in testicular cancer.Methods: A combined virtual screening protocol including pharmacophore modeling and molecular docking was used for screening potent dual-target ATM/HDAC2 inhibitors. In order to obtain the optimal lead compound, the dual ATM/HDAC2 inhibitory activity of the screened compounds was further evaluated using enzyme inhibition methods. The binding stability of the optimal compound to the dual targets was verified by molecular dynamics (MD) simulation. MTT assay and in vivo antitumor experiment were performed to validate antitumor efficacy of the optimal compound in testicular cancer.Results: Here, we successfully discovered six potent dual-target ATM/HDAC2 inhibitors (AMHs 1- 6), which exhibited good inhibitory activity against both ATM and HDAC2. Among them, AMH-4 showed strong inhibitory activity against both ATM (IC50 = 1.12 ± 0.03 nM) and HDAC2 (IC50 = 3.04 ± 0.08 nM). MD simulation indicated that AMH-4 binds to ATM and HDAC2 with satisfactory stability. Importantly, AMH-4 had significant antiproliferative activity on human testicular tumor cells, especially NTERA-2 cL.D1 cells, and no inhibitory effect on normal human testicular cells. In vivo experiments exhibited that AMH-4 was more effective than lartesertib and vorinostat in inhibiting the growth of NTERA-2 cL.D1 xenograft tumors with low toxicity.Conclusion: Overall, these results suggest that AMH-4 is an effective and low toxicity candidate for the treatment of testicular germ cell tumors.Keywords: ataxia telangiectasia mutated, histone deacetylase 2, dual-targeting inhibitors, testicular germ cell tumors, structure-based virtual screening